Medical Residency Subsidies and Physician Shortages - Cici McNamara; Mayra Pineda-Torres (Institute of Labor Economics (IZA), 2024)
We quantify the impact of federal subsidies for graduate medical education on primary care physician (PCP) supply by examining the impact of Section 5503 of the Affordable Care Act, which increased the number of residents that teaching hospitals in rural and high-need areas could receive subsidies for training. Instrumenting for selection into the program using its eligibility and allocation criteria, we find that the provision increased both the recruitment of residents into primary care and time spent at teaching hospitals in high-need areas, resulting in an increase in PCP supply in treated counties of 5.2 percent.
Keywords: I18; I28; J24; 330; Medicare; Affordable Care Act; primary care